Pengelolaan Sumber Daya Air (PSDA) Di Daerah Kering Gunungkidul Dengan Rain Driphonics System (RDS) - Sriyono, Edy; Reja Putra Jaya, (ReTII, 2024)
Most of the Gunungkidul district area is dry, barren rain-fed land with an area of ​​42,000 ha and a fairly high average rainfall of 1889.66 mm/year. So far, this rainfall can only be utilized during the rainy season, while during the dry season there is still a shortage of water because the excess rainwater flows directly on the surface and the rest is absorbed into the soil. The purpose of this study is to convert dry land into land for date palm plantations and their intercrops by maximizing the use of rainwater so that it is expected to maximize the socio-economic welfare of the surrounding community. With the Rain Driphonics System (RDS) method, the rainwater that falls is collected in reservoirs to then be channeled into the main reservoir pool, which is then pumped into the main reservoir pool and after adding liquid fertilizer from the water mixing tank, it is then channeled by gravity to the plantation land through the drip irrigation system. The analysis was carried out by calculating the amount of rainwater and then implementing it in the plantation demonstration plot. Based on the results of rainfall calculations, the highest mainstay discharge was obtained in January-II of 56.88 lt/sec, while the average water requirement for 40 main plants/date palms and intercrops was 0.08 lt/sec and by using a storage volume of 102 m3 and water savings, it can meet the needs for 1 year. So it can be concluded that by using RDS, it is proven that rainwater that falls in the rainy season can also be utilized in the dry season or in other words, rainwater that falls in the rainy season can be utilized throughout the year.